Relationship Between Academic Resilience with Academic Stress in Online Learning Among College Students in Kupang City - KAYUN, ROSALINA HELAKA; Limbu, Ribka; Wijaya, R. Pasifikus Ch. (Universitas Nusa Cendana, 2023)
Online learning that is implemented suddenly makes students experience fatigue related to excessive use of virtual communication platforms. If students are not able to face this extreme situation, students will experience stress. The stress in question is academic stress. The way for students to be able to cope with academic stress is that students must be resilient, which means they are able to survive in difficult situations. The difficult situation involved here is academic stress itself. The purpose of this study was to determine the relationship between academic resilience and academic stress online for students in Kupang City. This study uses a quantitative method with the type of research that is a correlational study. Respondents in this study were active students aged 18-25 years in Kupang City who carried out online totaling 334 students. The hypothesis proposed is H0 that is there is no significant relationship between academic resilience and academic stress and H1 is that there is a significant relationship between academic resilience and academic stress. The scale of this study uses two kinds of scales, namely the academic resilience scale and the academic stress scale. Data analysis using Spearman Rank. The results showed that there was no significant relationship between academic resilience and academic stress online for students in Kupang City. This can be seen at the value of R = -0.042 and P = 0.441 (p < 0.05). Therefore, it is concluded that H1 is rejected.